Cardioprotective Effects of Latifolin Against Doxorubicin-Induced Cardiotoxicity by Macrophage Polarization in Mice. Issue 6 (June 2020) - Zhang, Ni; Shou, Binyao; Chen, Lanying; Lai, Xiaoxiao; Luo, Yingying; Meng, Xiaowei; Liu, Ronghua
Abstract : Abstract: Latifolin, one of the major flavonoids extracted from lignum dalbergiae odoriferae, has been documented to protect the heart from acute myocardial ischemia induced by pituitrin and isoproterenol in rats and has also been found to inhibit inflammation. In this study, we aimed to investigate whether latifolin could protect the heart from doxorubicin (DOX)-induced cardiotoxicity and elucidate its underlying mechanisms. Male mice were treated with an intraperitoneal dose of DOX (20 mg/kg) plus oral latifolin at a dose of 50 or 100 mg/kg for 12 days. After exposure, we assessed cardiac function, myocardial injury, and macrophage polarization in excised cardiac tissue. Our results demonstrated that latifolin prevented DOX-induced cardiac dysfunction and produced macrophage polarization in mice challenged with latifolin. In cultured peritoneal macrophages, latifolin significantly reduced inflammatory cytokines ( P < 0.05). Furthermore, latifolin remarkably decreased the percentage of macrophage M1/M2 polarization ( P < 0.05). The results from the present study highlight the benefits of treatment with latifolin in DOX-induced cardiotoxicity, and the mechanism involved in mediating the polarization phenotype change of M1/M2 macrophages.